PELATIHAN FRONT END WEB DEVELOPER di SMK BINTANG NUSANTARA - Jupron; Santi Rahayu (Abdi Jurnal Publikasi, 2024)
SMK Link And Match, which is more familiarly called SMK LM, with educational services regarding software engineering, there is no web programming training for beginners. With that, this community service activity was held with Web programming training using HTML and CSS at SMK Link And Match. The time of this training was on Thursday, April 25, 2024 with 20 student participants. The training was held in the Multimedia Lab. The resource person presented the material with the help of a projector. The other committee as instructors guided the participants in practicing the material presented by the speakers. The implementation method is with the arrangement of preparatory activities, distributing consumption, opening the event, remarks, handing over mementos, presenting materials, questions and answers, distributing door prizes, group photos and closing the event. This training provides motivation for students in Web Programming training Using HTML and CSS.